The ways to improve the results of the pylorus-preserving gastric resection - V. V. Grubnik; R. P. Nikitenko; A. N. Kvasha; V. V. Mishchenko; N. D. Parfentieva (Клінічна хірургія, 2021)
Objective. To enhance the results efficacy of the pylorus-preserving gastric resection.